2010
DOI: 10.1097/mpa.0b013e3181bd93ce
|View full text |Cite
|
Sign up to set email alerts
|

Nardostachys jatamansi Protects Against Cerulein-Induced Acute Pancreatitis

Abstract: These results suggest that N. jatamansi attenuates the severity of AP and pancreatitis-associated lung injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 26 publications
2
15
0
1
Order By: Relevance
“…The dysregulation of IL-6 production or turnover can lead to chronic elevations of cytokines and many pathologic consequences [23]. In accordance with our previous report [4], the treatment of NJ inhibited the production of inflammatory mediators, such as TNF-a, IL-1b, and IL-6, in vivo and in vitro (Figs. 1 and 2).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The dysregulation of IL-6 production or turnover can lead to chronic elevations of cytokines and many pathologic consequences [23]. In accordance with our previous report [4], the treatment of NJ inhibited the production of inflammatory mediators, such as TNF-a, IL-1b, and IL-6, in vivo and in vitro (Figs. 1 and 2).…”
Section: Discussionsupporting
confidence: 83%
“…It has been used in the treatment of digestive diseases. Furthermore, the pharmacologic protective actions of NJ against Parkinson disease, liver damage, neuronal damage, and acute pancreatitis have been reported [4,20]. In the present study, we observed the protective effects of NJ in LPS-induced endotoxin shock.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…아토피피부염을 크게 濕熱 俱盛型, 脾虛濕盛型, 血虛風燥型으로 변증 분류하는 . 감송향의 성분은 valeranone, nardosonone, nardostachone, 1-aristilene-2-one, patchouli alcohol, pinene, oleeanolic acid, b-sitisterol 등을 함유하였고 [4][5][6]30) , 감송 향의 효능에 관한 연구는 대부분 신경계와 관련된 연 구로서 뿌리 및 근경 (Nardostachytis rhizoma) 추출물의 진정효과 31) , 신경세포 분화와 관련된 보고 [32][33][34][35] , 급성 췌 장염 억제 16,17,36) , 항산화 및 항스트레스 작용 37,38) , 항박 테리아, 항진균작용 39) , 염증 및 면역에 관한 보고 …”
Section: Tnf-α 생성 조절에 Nj의 효과를 측정하기 위하여unclassified
“…The deactivation or extermination the PSCs is well-known treatment of CP (6). We already have reported that Nardostachys jatamansi (NJ) has protective effects on acute pancreatitis, and sepsis (7,8). We have used the root decoction in the evaluation of NJ's effects.…”
Section: Introductionmentioning
confidence: 99%